Use of balance exercises for dynamic stability in basketball injuries - Dubenová, L.; Líška, D.; Vavro, M. (Kinesiologia Slovenica, 2021)
Basketball is a very popular team sport that is played around the world with a high prevalence of lower limb injuries. Therefore, we have decided to test the effect of balance exercises on the dynamic stability of the lower limbs. We performed dynamic balance testing on a 30-member group of young basketball players of the same average age, playing the cadet competition of the Slovak Championships - West Region. The control group consisted of 16 basketball players. For testing, we have chosen a test for the dynamic stability - Y balance test (YBT). Testing of the dynamic stability of the lower limbs with hands placed freely next to the body in the intervention group was statistically significant (p <0.05). We have also noticed statistically significant improvement in the intervention group (p<0.05). Balance exercises have been associated with improved dynamic stability in young basketball players.